HIZBUL WATHAN DAN DISIPLIN ANAK: LEBIH DARI SEKEDAR EKTRAKURIKULER - Rahma Aliffiani; Juhairiah Juhairiah; Saipul Hadi (Fakultas Studi Islam UNISKA MAB Banjarmasin, 2025)
This research is motivated by the existence of extracurricular activities aimed at developing students' potential and skills outside the formal curriculum, thereby supporting the achievement of academic success and fostering positive character development among learners. This particular extracurricular activity is called Hizbul Wathan, which is specifically found in Muhammadiyah educational institutions. The Hizbul Wathan extracurricular activity. Therefore, this study seeks to describe how the Hizbul Wathan extracurricular activities at Muhammadiyah 1 Tenggarong Elementary School contribute to the development of students' positive character, particularly in terms of self-discipline. This research uses a descriptive qualitative approach, with data collection techniques that include observation, interviews, and documentation. The data sources are divided into two types: primary data, obtained from the instructors (referred to as Ramanda and Ibunda) and students; and secondary data, obtained from other parties involved in the Hizbul Wathan extracurricular activities. The results of the study indicate that the Hizbul Wathan extracurricular activities at Muhammadiyah 1 Tenggarong Elementary School have a positive impact on the development of self-discipline among participating students. These activities—both structured and unstructured—include various components such as marching drills, cipher codes, knot-tying, leadership games, organizational skills training, and outdoor activities. All of these are designed and implemented to foster and enhance the value of discipline in students. In addition, the role of the instructors (Ramanda and Ibunda) is highly significant in guiding and motivating students to apply discipline in their daily lives.